Recommendations on improving the defense resource management system and defense management of Ukraine, taking into account the experience of foreign countries - Semenenko, Oleh; Skurinevska, Lesia; Ostapets, Oleh; Shcherbliuk, Serhii (Social Development and Security, 2023)
Purpose: is to determine, based on the experience of foreign countries, general recommendations for improving the defense resource management system and defense management of Ukraine, as well as recommendations for practical improvement of the current defense resource management system at the level of the Armed Forces of Ukraine. Method: the main methods of research are methods of analysis and synthesis, methods of military economic theory, induction and deduction, as well as comparison, formalization, abstraction. Findings: the main reasons for the need to improve the system of defense management and management of defense resources of Ukraine are formed; the general principles and characteristics of the functioning of these systems in foreign countries are defined; formed recommendations on improving the theoretical and practical basis of the functioning of defense management systems and defense resources management at the state level and at the level of the Armed Forces of Ukraine; the main prospects for further improvement of these systems are defined. Theoretical implications: the main results of research on the topic of the article are: determination of the main problematic issues of the development of defense management systems and defense resource management at the state level and the level of the Armed Forces of Ukraine, as well as a number of recommendations for improving the theory and practice of the functioning of these systems. Paper type: analytical, theoretical and methodical, descriptive.